Infographic Design As An Effective Communication Model For Volcano Eruption Disaster's Socialization - Aryo Bayu Wibisono; Bayu Suryo Ridho Saputro; Puspita Sari Sukardhani (Jurnal Ilmu Komunikasi, 2018)
Indonesia is an archipelago surrounded by cluster of volcanoes known as the ring of fire. Indonesian volcanoes located within the range of the fire ring has the natural disaster potential of volcano eruption. The main concern in this study is the number of tribes people / communities in Indonesia who live in the slopes of the volcano, and the other factor is the fact that people living on the slopes are mostly came from low-education background, making it difficult for the government to socializing the danger. This study will discuss the design and stages of appropriate communication to convey the volcano eruption socialization to the tribes that live in the volcano area using the visual language of infographic. The case studies of this research will take a sampling of the Tengger tribe who inhabit the area of Mount Bromo as one of the active volcano on the Java island, Indonesia. The data retrieving methods used in this study are in-depth interviews, direct observation, and the collection of related books and journal literature. Contributions and model of this research is expected to be applicable to inform people who inhabit the volcano areas in Indonesia of the proper action to take when the volcano eruption strikes.